Opening the Classroom Door - A Survey of Middle Grades Teachers Who Mentor Preservice Teachers— Lessons from Clinical Partnerships and Implications for Practice - Steven L. Turner; Carie C. Greene (Middle Grades Review, 2017)
Mentor teachers that participate in school-university clinical experiences have a unique opportunity to support preservice middle grades teachers’ development and improve the schooling of young adolescents. This article investigates an early clinical experience and presents data from a survey of 38 middle school teachers who served as mentor teachers. Findings address how middle grades teachers view their role as mentors, their perceptions of the clinical experience as a collaborative learning partnership, and concludes with suggestions to improve clinical experiences for preservice middle grades teacher candidates.
Keywords: Clinical Experiences; preservice teachers; mentoring